Reproducibility of BOLD, perfusion, and CMRO2 measurements with calibrated-BOLD fMRI - Leontiev, Oleg; Buxton, Richard B. (NeuroImage (Orlando, Fla.), 2007)
The coupling of changes in cerebral blood flow (CBF) and cerebral metabolic rate of oxygen (CMRO2) during brain activation can be characterized by an empirical index, n, defined as the ratio between fractional CBF change and fractional CMRO2 change. The combination of blood oxygenation level dependent (BOLD) imaging with CBF measurements from arterial spin labeling (ASL) provides a potentially powerful experimental approach for measuring n, but the reproducibility of the technique previously has not been assessed. In this study, inter-subject variance and intra-subject reproducibility of the method were determined. Block design %BOLD and %CBF responses to visual stimulation and mild hypercapnia (5% CO2) were measured, and these data were used to compute the BOLD scaling factor M, %CMRO2 change with activation, and the coupling index n. Reproducibility was determined for three approaches to defining regions-of-interest (ROIs): 1) Visual area V1 determined from prior retinotopic maps, 2) BOLD-activated voxels from a separate functional localizer, and 3) CBF-activated voxels from a separate functional localizer. For estimates of %BOLD, %CMRO2 and n, intra-subject reproducibility was found to be best for regions selected according to CBF activation. Among all fMRI measurements, estimates of n were the most robust and were substantially more stable within individual subjects (coefficient of variation, CV=7.4%) than across the subject pool (CV=36.9%). The stability of n across days, despite wider variability of CBF and CMRO2 responses, suggests that the reproducibility of blood flow changes is limited by variation in the oxidative metabolic demand. We conclude that the calibrated BOLD approach provides a highly reproducible measurement of n that can serve as a useful quantitative probe of the coupling of blood flow and energy metabolism in the brain.